Metabolomics and molecular networking analyses in Arabidopsis thaliana show that extracellular self-DNA affects nucleoside/nucleotide cycles with accumulation of cAMP, cGMP and N6-methyl-AMP. (December 2022) - Lanzotti, Virginia; Grauso, Laura; Mangoni, Alfonso; Termolino, Pasquale; Palomba, Emanuela; Anzano, Attilio; Incerti, Guido; Mazzoleni, Stefano
Abstract: Extracellular DNA (exDNA) widely occurs in the environment due to release by either cell lysis or active secretion. The role of exDNA in plant-soil interactions has been investigated and inhibitory effects on the growth of conspecific individuals by their self-DNA have been reported. Transcriptome analysis in the model plant Arabidopsis thaliana showed a clear recognition by the plant roots of self- and nonself-exDNA, with inhibition occurring only after exposure to the former. In this study, an untargeted metabolomics approach was used to assess at molecular level the plant reactions to exDNA exposure. Thus, the effects on the metabolites profile of A. thaliana after exposure to self- and nonself-exDNA from plants and fish, were studied by NMR, LC-MS, chemometrics and molecular networking analyses. Results show that self-DNA significantly induces the accumulation of RNA constituents (nucleobases, ribonucleosides, dinucleotide and trinucleotide oligomers). Interestingly, AMP and GMP are found along with their cyclic analogues cAMP and cGMP, and in form of cyclic dimers (c-di-AMP and c-di-GMP). Also methylated adenosine monophosphate (m6AMP) and the dimeric dinucleotide N-methyladenylyl-(3'→5') cytidine (m6ApC) increased only in the self-DNA treatment. Such striking evidence of self-DNA effects highlights a major role of exDNA in plant sensing of its environment. Graphical abstract: Metabolomics and molecular networking of Arabidopsis thaliana showed differential and specific accumulation of RNA constituents and analogues only after exposure to the plant self-DNA. Image 1 Highlights: Arabidopsis thaliana metabolites during self- and nonself-DNA exposure are analysed. Combined approach of NMR, LC-MS, chemometrics and molecular networking is used. Self-DNA exposure induced a significant accumulation of specific RNA constituents. Cyclic AMP and GMP, and N6 methylated adenosine occur only in self-DNA treatment. This is the first metabolomic study on different effects of self- and nonself-exDNA.